Respuesta :

Answer:

(x - 8)(2x + 3)

Step-by-step explanation:

To factor a polynomial of the form

ax² + bx + c,

follow these steps:

1) Multiply ac together.

2) Find 2 factors of ac that add to b. Call these factors p and q.

3) Break up the middle term of the polynomial into px + qx.

4) Factor by grouping.

Now let's follow the steps above with your problem.

You are given the polynomial

2x² - 13x - 24,

so a = 2, b = -13, and c = -24

1) Find ac.ac is the product 2(-24) = -48

2) Now we need to find 2 factors of -48 that add to b, -13.

I know that 48 = 3 × 16, so if we use -16 and 3 for the two numbers, we have

-16 + 3 = -13

and -16 × 3 = -48.

3) Now we break up the middle term of the polynomial, -13x, into -16x + 3x.

The polynomial is now

2x² - 16x + 3x - 24

4) We factor the polynomial by grouping. To factor by grouping, you factor a common factor out of the first 2 terms and factor out a common factor out of the last two terms.

2x² - 16x + 3x - 24 =

= 2x(x - 8) + 3(x - 8)

We now see the common factor of x - 8, so we factor that out.

= (x - 8)(2x + 3)

Answer: (x - 8)(2x + 3)